Obesidad como factor de riesgo de asma en niños. Centro de Alergias Muñoz, 2017- 2019 - Guamán Cali, Fernanda Esthefania (2020)
Objective: To determine the impact of obesity as a risk factor in the development of asthma in children between 5 and 10 years of age, Muñoz Allergy Center, January 2017-December 2019. Material and Methods: The study was conducted based on the research methodology with a descriptive, retrospective and cross-sectional study, a series of cases and controls, in a universe of 240 patients, obtaining data from the review of patient records and electronic medical records of the Asthma and Allergy Center, Muñoz. Results: Of the 240 patients in the study period, 101 patients registered with a diagnosis of bronchial asthma, where the age of predominance is five years with 47 cases (19.58%), male sex 57 cases (23.75%), there are 41 cases of patients with healthy BMI (17.08%), 28 patients (11.66%) with overweight, the history of exclusive breastfeeding prevails with 39 cases (16.25%), mixed feeding with 33 cases (13.15%), exposure to pets stands out with 83 cases (34.5%) and exposure to tobacco smoke with 81 cases (33.75%), it was evident that there is no family medical history in 53 cases (22.08%) and in the history of atopic march, atopic dermatitis is the most prominent with 48 cases (20%). Conclusion: According to research carried out in children from 5 to 10 years of age in the Muñoz Allergy Center of the period January 2017- December 2019, the majority of asthmatic patients studied have a healthy BMI followed by overweight and risk of overweight. It constitutes than in the long term, if the lifestyle of patients is not improved will become obese. It is, therefore, essential to raise awareness in society and indeed to educate the family nucleus about the importance of medical and nutritional check-up.